Changing scenarios in Bajo de la Quinta (San Matías Gulf, Northern Patagonia, Argentina): Impact of geomorphologic processes in subsistence and human use of coastal habitats - Favier Dubois, Cristian Mario (2011)
As in other parts of the world, the northern coast of the San Matías Gulf (Northern Patagonia, Argentina) has undergone remarkable changes after the Middle Holocene sea level maximum. By means of an interdisciplinary work, the geomorphologic evolution of Bajo de la Quinta coastal hollow was reconstructed since ca. 600014CBP, when the oldest human occupation of the area was detected. Main recorded changes in coastal configuration seem to have had a noticeable influence in both the use of marine resources along time by native hunter-gatherer groups, and the preservation of the archaeological evidence. With respect to the first issue, changes in human paleodiets and fishing practices could be related with the sedimentary filling and rectification of this littoral after the high marine level scenario. This study highlights the importance of reconstructing past scenarios of human activities for archaeological interpretation, in particular when studying high dynamic environments such as the coastal landscape.